IR and 1H NMR Spectra of Tin(II) Complexes with 1-Substituted Tetrazoline-5-thiones - PANDEY, R.N. (Asian Journal of Chemistry, 2010)
Complexes of phenyl, ortho-tolyl, meta-tolyl and p-chlorophenyl derivatives of 1-substituted tetrazoline-5-thione have been prepared with Sn(II) and characterized on the basis of analytical, infrared, electronic and 1H NMR spectral studies. All the complexes have general formula [Sn(ligand)4(OH)2] having trans- octahedral configuration. Metal-ligand vibrations in far IR have also been located and assigned.